Analisis Daya Serap Air Paving Block Dengan Polyethylene Terephthlate Sebagai Pengganti Semen - Al Hidayat, Fauzi; Indriani, Andi Marini; Utomo, Gunaedy; Harami, Fachruddin (Journal of Applied Civil Engineering and Infrastructure Technology, 2025)
Plastic waste is one of the main challenges faced by Indonesian society. Plastic drinking bottles are one of the largest sources of waste, and it is estimated that the total amount of plastic waste worldwide will reach 12,000 million tons by 2050. So there needs to be an effort to recycle the plastic. In this study, PET plastic was used as a substitute for cement in paving blocks. The purpose of this research is to evaluate whether paving blocks using a mixture of PET plastic and sand can meet the requirements of water absorption according to SNI 03-0691-1996 standard. The comparison between PET plastic and sand is 10%: 90%, 20% : 80%, 30% : 70%, 40% : 60%, 50% : 50%, with temperatures of 240°C, 260°C, 280°C. The absorption of paving blocks by utilizing Polyethylene Terephtalate (PET) plastic as a substitute for cement decreased as the PET plastic increased. The lowest absorption was found in the 30% variation at 280°C with a value of 0.18%. The 10% plastic variation at each different temperature obtained more than 10% absorption, where the results did not meet the quality of SNI 03-0691 (1996). While the addition of 20%, 30%, 40% and 50% plastic obtained a value below 1% which means it meets the quality of A in SNI 03-0691 (1996).